2013
DOI: 10.4103/2229-5178.110586
|View full text |Cite
|
Sign up to set email alerts
|

Smokers′ hair: Does smoking cause premature hair graying?

Abstract: Aims:To determine if there is a significant association between premature hair graying and cigarette smoking.Materials and Methods:A cross-sectional observational study was conducted in a nonclinical setting on 207 participants on August 24 until 25, 2010. Participants were classified into two groups [premature hair graying (PHG) and normal hair graying]. PHG was defined as the first appearance of gray hair before the age of 30. Data were collected using an interview questionnaire and measurements of body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
0
22
1
Order By: Relevance
“…12 In the analysis of the severity of PHG, excluding smoking, family history and obesity showed significant associations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…12 In the analysis of the severity of PHG, excluding smoking, family history and obesity showed significant associations.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies that reported an association between smoking and PHG also failed to show a correlation between smoking and the severity of PHG. 12,25 To confirm whether smoking affects the severity of PHG, a further study including participants with a wide range of ages is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of scalp regional graying development did not essentially differ between sexes but more males (75.5%) had hair graying initially involving the parietal areas than in the females whose regional graying patterns were mostly equally distributed all over the scalp regions. behaviors such as smoking and sedentary life style were reported by a huge proportion of participants [8,15,16] whereas some other studies established a weak association or no association at all [17]. The consequential psychological effects to the sufferers were enormous among the participants of the present study.…”
Section: Resultsmentioning
confidence: 51%
“…In the quest to search for preventable risk factors leading to or associated with PHG, some studies have proposed smoking and other forms of tobacco use, a positive family history, UV radiations and medical and illicit drugs as independent risk factors [6][7][8] while other studies contradict this view [9]. Hair plays a vital role in the physical appearance and identity and has a further covert role in social communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation